Modeling tumor growth using fractal calculus: Insights into tumor dynamics - Golmankhaneh, Amirreza Khalili; Tunç, Sümeyye; Schlichtinger, Agnieszka Matylda; Asanza, Dachel Martinez; Golmankhaneh, Alireza Khalili (Elsevier Ireland Ltd, 2024)
Important concepts like fractal calculus and fractal analysis, the sum of squared residuals, and Aikaike's information criterion must be thoroughly understood in order to correctly fit cancer-related data using the proposed models. The fractal growth models employed in this work are classified in three main categories: Sigmoidal growth models (Logistic, Gompertz, and Richards models), Power Law growth model, and Exponential growth models (Exponential and Exponential-Lineal models)”. We fitted the data, computed the sum of squared residuals, and determined Aikaike's information criteria using Matlab and the web tool WebPlotDigitizer. In addition, the research investigates “double-size cancer” in the fractal temporal dimension with respect to various mathematical models.
Keywords: Fractal Analysis; Fractal Calculus; Fractal Cancer Growth Models; Fractal Gompertz Growth Model; Fractal Richards Growth Model; Fractal Temporal